CHALLENGES OF TEACHING INDONESIAN FOR FOREIGN SPEAKERS (BAHASA INDONESIA BAGI PENUTUR ASING/BIPA) IN AUSTRIA DURING THE PANDEMIC COVID-19 - Robita Ika Annisa; M. Maman Sumaludin (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
Out of the 41 countries that run the Indonesian Language Learning Program for Foreign Speakers, in collab with the Language Development and Cultivation Agency under the auspices of the Ministry of Education and Culture of the Republic of Indonesia, Austria is one of them. When the learning went online due to the Covid-19 pandemic, teachers, students, and Indonesian Language for Foreign Speakers class organizers, the Indonesian Embassy in Vienna together with the University of Vienna, faced challenges. Based on this background, this study aims to describe the challenges of Indonesian Language teachers for Austrian when they implement the learning by online. This research uses a qualitative approach with the type of case study research. The writer got the data through interviews and questionnaires to Indonesian Language teachers for Austrian from winter 2020 to winter 2021 and was strengthened by literature studies. As a result, teachers face various challenges such as technical issues with the devices and internet networks, and time gaps between Indonesia and Austria. Online classes are widely open for everyone in Austria, but at the same time amount of students is also rising because some of them preferred to do it face to face, and the difficulty of managing online classes with high heterogeneity. The efforts made by teachers in responding to these challenges include varying learning activities, opening communication spaces with students through various platforms, utilizing various online platforms that are relevant to learning topics, and organizing and inviting guest lecturers for speaking class and cultural topics.